A qualitative meta-synthesis of evidence (meta-ethnography) exploring the personal experiences of gastrostomy tube in neurodegenerative diseases: a case of motor neurone disease. Issue 18 (28th August 2022) - Lisiecka, Dominika; Kearns, Aine; Bourke, Fiona; Lawson, Ian; Muir, Cath
Abstract: Purpose: The lived experiences of a gastrostomy tube (GT) in adults with neurodegenerative diseases (NDDs) are not well understood. The aim of this qualitative meta-synthesis was to review and synthesise the available evidence to inform clinical practice and identify research gaps. Methods: Meta-ethnographic synthesis of qualitative studies was conducted with systematic searching of eight databases from inception to March 2021. Qualitative studies reporting personal experiences of GTs in adults with NDDs were identified. New theories were developed during translation of concepts from each study and combined as a "line-of-argument" synthesis. Patient and public involvement was incorporated as two of the authors are living with an NDD and a GT. Results and conclusions: Of 2863 unique records identified, only nine fulfilled the review criteria. All studies recruited participants with motor neurone disease (MND); no other NDDs were represented. Two main themes emerged: decision making and living with GT. Decision making was the predominant theme and data regarding living with GT were sparse. There is limited research on the lived experience of a GT in adults with NDDs. The lived experience of GT in MND is complex and individualised. Future research is indicated to inform clinical practice. Implications for rehabilitation: Evidence related to the lived experiences of gastrostomy tube (GT) in neurodegenerative diseases (NDDs) is lacking especially in relation to the time after GT insertion. Decision making in relation to GT is a complex and individualised psychological process for some people, while others perceive no decisional conflict. Support from healthcare professionals is crucial during the decision-making time and should not cease after GT insertion. Support from healthcare professionals can help resolve any clinical complications and also incorporate GT into everyday routines. Healthcare professionals should be aware that their views on the benefits and problems related to GT may differ to those of individuals with a NDD.